Pengaruh Advertising Intensity terhadap Shareholder Value melalui Customer Satisfaction dan Brand Equity pada Perusahaan yang Terdaftar di Bursa Efek Indonesia - Monica Jiewanto; Josua Tarigan (Business Accounting Review, 2016)
This study aimed to know the influence of advertising intensity, customer satisfaction, and brand equity on shareholder value on companies of all sectors listed in Indonesia Stock Exchange (IDX). This study encompassed samples of 99 firm-year, which were comprised of 21 listed firms in IDX whose brand appeared on the published index of Indonesian Customer Satisfaction Award (ICSA) and Indonesia Best Brand Award (IBBA) of SWA magazine during 2010-2014. According to the data processed and analysed by using PLS, this study revealed that advertising intensity, customer satisfaction, and brand equity affected shareholder value positively and significantly.